Back Cover: Synthesis, Characterization, Self‐Assembly, Gelation, Morphology and Computational Studies of Alkynylgold(III) Complexes of 2, 6‐Bis(benzimidazol‐2′‐yl)pyridine Derivatives (Chem. Eur. J. 32/2014). Issue 32 (4th August 2014) - Yim, King‐Chin; Lam, Elizabeth Suk‐Hang; Wong, Keith Man‐Chung; Au, Vonika Ka‐Man; Ko, Chi‐Chiu; Lam, Wai Han; Yam, Vivian Wing‐Wah
<x xml:space="preserve">Abstract</x> A novel class of alkynylgold(III) complexes with dianionic ligands derived from 2, 6‐bis(benzimidazol‐2′‐yl)pyridine has been synthesized and characterized. One of the complexes has been found to show interesting gelation properties, which may open up new horizons in the applications of low‐dimensional gold(III) complexes in supramolecular assembly. For more information, see the Full paper by V. W.‐W. Yam et al. on page 9930 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>